Rhodium-catalysed selective C–C bond activation and borylation of cyclopropanes. Issue 10 (25th January 2021) - Wang, Yandong; Bai, Jingyi; Yang, Youqing; Zhao, Wenxuan; Liang, Yong; Wang, Di; Zhao, Yue; Shi, Zhuangzhi
Abstract : Transition metal (TM)-catalysed directed hydroboration of cyclopropanes which facilitates the construction of complex alkylboronates is an essential synthetic methodology. Abstract : Transition metal (TM)-catalysed directed hydroboration of aliphatic internal olefins which facilitates the construction of complex alkylboronates is an essential synthetic methodology. Here, an efficient method for the borylation of cyclopropanes involving TM-catalysed directed C–C activation has been developed. Upon exposure to neutral Rh(i )-catalyst systems, N -Piv-substituted cyclopropylamines (CPAs) undergo proximal-selective hydroboration with HBpin to provide valuable γ-amino boronates in one step which are otherwise difficult to synthesize by known methods. The enantioenriched substrates can deliver chiral products without erosion of the enantioselectivities. Versatile synthetic utility of the obtained γ-amino boronates is also demonstrated. Experimental and computational mechanistic studies showed the preferred pathway and the origin of this selectivity. This study will enable the further use of CPAs as valuable building blocks for the tunable generation of C–heteroatom or C–C bonds through selective C–C bond activation.